Immunotherapy and Epigenetic Pathway Modulation in Glioblastoma Multiforme - Chin, Christopher; Lunking, Emma S.; de la Fuente, Macarena; Ayad, Nagi G. (Frontiers in Oncology, 2018)
Glioblastoma Multiforme (GBM) is the most common malignant primary brain tumor. Despite aggressive multimodality treatment it remains one of the most challenging and intractable cancers [1]. While current standard of care treatment for GBM is maximal safe surgical resection, systemic chemotherapy with Temozolimide (TMZ), and radiation therapy, the current prognosis of GBM patients remains poor, with a median overall survival of 12-15 months [2] [3]. Therefore, other treatments are needed to provide better outcomes for GBM patients. Immunotherapy is one of the most promising new cancer treatment approaches. Immunotherapy drugs have obtained regulatory approval in a variety of cancers including melanoma [4], Hodgkin lymphoma [5] and non-small cell lung cancer [6]. The basis of immunotherapy in cancer treatment is linked to stimulating the immune system to recognize cancer cells as foreign, thereby leading to the eventual elimination of the tumor. One form of immunotherapy utilizes vaccines that target tumor antigens [7], while other approaches utilize T-cells in patients to stimulate them to attack tumor cells [8]. Despite intensive efforts all approaches have not been overtly successful [9], suggesting that we need to better understand the underlying biology of tumor cells and their environment as they respond to immunotherapy. Recent studies have elucidated epigenetic pathway regulation of GBM tumor expansion [10], suggesting that combined epigenetic pathway inhibition with immunotherapy may be feasible. In this review, we discuss current GBM clinical trials and how immune system interactions with epigenetic pathways and signaling nodes can be delineated to uncover potential combination therapies for this incurable disease.